Knowledge, attitudes, and practices of parents toward sexuality education for primary school children in China - Zhang, Wenjing; Yuan, Yuzhi (Frontiers in Psychology, 2023)
This cross-sectional study provides insight into the perceptions of Chinese parents of primary school children with respect to sexuality education. A sample of 19745 parents were surveyed using online questionnaire in Beijing, Tianjin and Hebei in China. SPSS version 23.0 was used for data analysis. In this study, nearly 90% parents had positive attitudes toward children’s sexuality education in primary schools. However, Chinese parents had limited knowledge of sexuality education. More than 60% parents did not know sexuality questions that children may be encountered at different ages and have any accurate information on child sexual abuse prevention education. Although approximately 70% of parents (both fathers and mothers) reported that they had made use of the television and the internet resources to talk with their children about sexuality and 63% reported that they had read books with their children about sexuality, less than 30% reported using appropriate terminology with their children on sexuality education and only 40% reported talking to their children about sexuality comfortably. The multivariate linear regression equation showed some factors associated with parents’ practices in sexuality education, including parental knowledge, attitudes, their experience in receiving sex education in childhood and their educational level. Findings from this study suggest that it is important to develop culturally relevant training programs for parents of primary schools in Chinese society. The implications and limitations of these findings are discussed.